Relative prices and monetary policy information variables: Long run evidence from Finland - Antti Ripatti; Jouko Vilmunen (Bank of Finland, 1995)
Under certain assumptions, the permanent income model yields the result that prices of different products share common stochastic trends.We construct four price series from the components of the consumer price index, combine this four variable system with various macroeconomic variables, such as broad money (M2), nominal exchange rates, import and export prices in domestic currency etc., with the ultimate hope of capturing empirical regularities between this price structure and the proposed macroeconomic information.It is found that broad money, money market and bond yield indices, nominal exchange rates and import prices contain long-run information about the price level.We also find that the common trends of price groups cointegrate with the broad monetary aggregate and the money market yield index, indicating that these variables might be the driving forces of underlying inflation.
URN:NBN:fi:bof-20140807563
Keywords: 330